Multidimensional Evaluation of Brown Shrimp Trawling Fisheries on the Amazon Continental Shelf - Araújo, Janayna Galvão; Mello Filho, Adauto dos Santos; Peixoto, Ualerson Iran; Bentes, Bianca; Santos, Marcos Antonio Souza dos; Dutka-Gianelli, Jynessa; Isaac, Victoria (Frontiers in Marine Science, 2022)
Brown shrimp (Penaeus subtilis) trawling in the northern coastal waters of Brazil is an industrial fishing activity with a share in the international market and an important resource in the fishery market. Due to the scarcity of updated information on this practice and owing to its complexity, it is difficult to have a measurement of all dimensions of the development of this fishery, whether they are ecological, economic, or social-institutional. The present paper uses an assessment tool focused on data-poor fishery systems, the Fishery Performance Indicators (FPIs), to assess the multidimensional conditions of this fishery. The indicators were assessed between 2019 and 2020, and the metrics were based on public official data, scientific publications, in loco consultations with production agents, and databases of research projects. Results showed that the critical points of this activity are primarily related to the ecological indicator (1.75), which obtained a lower score compared to other fisheries assessed using the same methodology. This is due to its low selectivity, which results in high by-catch volumes and discards. The limited participation of productive chain actors also restrains the efficacy of management measures, which hampers successful resource management. This issue maximizes other setbacks throughout the productive chain, such as economic and social factors.